Developing sustainable food systems, policies, and securities - Obayelu, Abiodun Elijah; Obayelu, Oluwakemi Adeola (2020)
"This book provides multidisciplinary perspectives on how to develop sustainable food systems, policies, and securities"--Provided by publisher".
Keywords: Sustainable agriculture; Food security; Women in agriculture; Land use, Rural